Assessing stakeholder perceptions of effectiveness of Namibia's communications regulatory framework - Stanley, Shanapinda (My University, 2014)
Communications regulatory frameworks are established to achieve affordable pricing, consumer welfare, innovation and competition. A regulatory framework is therefore endowed with regulatory governance measures and regulatory incentives to enable it to achieve these purposes. In applying these measures and incentives, the framework becomes effective, or ineffective, if the framework fails. The purpose of this qualitative exploratory study was to assess the perceptions of the stakeholders on the effectiveness of the types of governance measures and incentives implemented in Namibia because stakeholders are involved in the success or failure. The study of perceptions are important because they offer insight of informed stakeholders of how policies, laws and regulations are implemented for whom those policies, laws and regulations are designed, implemented and meant to impact. Such insights can inform the design of recommendations on how these measures and incentives can be improved to make the regulatory framework more effective, as it has done in this study. One of the main findings of the research was the perceived conflict of interests between the ICT policy role of the Ministry of ICT and its shareholder role over Telecom Namibia, negatively impacting on competition and putting privately owned licensees at a market disadvantage. The conclusion was that this regulatory governance design measure conflicts with the regulatory framework and requires legislative amendment and a re-design of the framework to achieve the regulatory purpose of competition and improve Namibia’s regional and global competitiveness.
Keywords: Telecommunication policy; Competition; Consumer behaviour; Namibia